ANALISIS PENGEMBANGAN ARMADA PERIKANAN TANGKAP DI KABUPATEN KUPANG NUSA TENGGARA TIMUR - Deselina M.W. Kaleka; Budhi H. Iskandar; Daniel R. Monintja; Mulyono S. Baskoro (Buletin PSP, 2007)
This research discusses on the development analysis of fishing fleet in Kupang Regency, Nusa Tenggara Timur. The objective of the research is to develop a conceptual model in developing fishing fleet based on CCRF.The data from representatives sources have been collected through a survey methods by using questionnaires. In order to achieve the research objective, some methods such as SWOT, LGP, AHP and scoring on CCRF have been used to analyze the data.The result show that based on the analysis and combining with certain scenarios that used in the research, fishing unit that prostective to be developed gradually are hand line (pancing ulur), trap (bubu) and long line (rawai), meanwhile purse seine can be developed within maximum number of fleet